Psychopathology and hormonal disturbances in eating disorders (Italian Journal of Public Health, 2008)
Background: Our aim was to study the relationship between hormonal disturbances and psychopathology in Eating Disorders (ED).Methods: Forty-nine women diagnosed as Eating Disorders according to DSM-IV were subjected to control plasma levels of TSH, FT3, FT4, LH, FSH, 17beta-estradiol, prolactin, cortisol, DHEAS, GH and IGF-1. They were also administered by SCL-90R, BAT, DES II questionnaires. We applied multivariate regression models.Results: Our results highlight a statistically significant relation between LH, FSH and prolactin decreased levels, mood and thought disturbances (subscales 3, 5, 7, 8 and 9 of SCL-90r) which are associated to Body Attitude ( BAT total scale) and Dissociative Experiences (DES II total scale).Conclusions: Decreased sexual hormones levels could have a role in ED psychological disturbances, not inquired yet.
Keywords: Eating disorders; hormonal disturbances; neuropsychological functions